2012
DOI: 10.1016/j.ijbiomac.2011.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Antinociception of β-d-glucan from Pleurotus pulmonarius is possibly related to protein kinase C inhibition

Abstract: β-D-Glucan, a polysaccharide isolated from an edible mushroom Pleurotus pulmonarius (Fr.) Quel., presented antinociceptive activity in mice. This study evaluated the involvement of transient receptor potential (TRP) channels and protein kinase C (PKC) on antinociceptive effect of a (1→3),(1→6)-linked β-D-glucan (GL) in mice. Intraperitoneal administration of GL potently inhibited nociceptive responses induced by intraplantar injections of capsaicin, cinnamaldehyde, menthol, acidified saline and phorbol myrista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 34 publications
1
27
0
Order By: Relevance
“…The amount of time that the animal spent licking the injected paw was recorded with a chronometer over 5 min (for capsaicin or cinnamaldehyde) or 20 min (acidified saline and menthol) and used as an index of nociceptive behavior intensity. The doses were based on previous studies [41, 42]…”
Section: Methodsmentioning
confidence: 99%
“…The amount of time that the animal spent licking the injected paw was recorded with a chronometer over 5 min (for capsaicin or cinnamaldehyde) or 20 min (acidified saline and menthol) and used as an index of nociceptive behavior intensity. The doses were based on previous studies [41, 42]…”
Section: Methodsmentioning
confidence: 99%
“…In light of these considerations, polysaccharides recently became the focus of studies for the treatment of several disturbs. Recent works demonstrated that polysaccharides isolated from different sources exhibited important pharmacological activities, as antitumoral, immunomodulatory, antinociceptive and gastroprotective [30][33]. Interestingly, our group showed that the polysaccharide rhamnogalacturonan (RGal) isolated from A. oleracea protected the gastric mucosa against acute lesions induced by ethanol in rats, with an ED 50 of 1.5 mg/kg when administered by oral route.…”
Section: Discussionmentioning
confidence: 96%
“…Investigations have proved the anti-oxidative properties of polysaccharides obtained from P. tuber-regium (Wu et al, 2014). A β-glucan obtained from P. pulmonarius has been found to exhibit analgesic and anti-inflammatory effects (Baggio et al, 2012).…”
Section: Polysaccharidesmentioning
confidence: 99%